Scooby-Doo! World of Mystery 31 Germany - Worms - Creative Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
Mystery Inc. travel to worms in Germany and uncover a mystery involving dwarves ,ghosts and a bank...
Keywords: Juvenile literature-Fiction